Vilne, Vilne undzer Meka: A City on the Border between Old and New, East and West - Krutikov, Mikhail (Colloquia, 2021)
One of the key features of the image of Vilnius is its position on a symbolic spatial and chronological border. Depending on the ideological agenda of a particular imperial or national discourse, Vilnius can be located on the western or the eastern frontier of the imaginary imperial realm (Russian or German respectively), or as a historic national capital (for Poles, Lithuanians and Belarusians). Correspondingly, different national and imperial narratives evaluated particular historical periods differently, usually portraying the more remote past positively, as opposed to the most recent past. The Russian city guide by Flavian Dobrianskii and the German books by Paul Weber and Paul Monty, published respectively before and during the First World War, described the city from two opposite perspectives using the same conceptual opposition of East versus West. Unlike these dichotomous representations, Jewish Modernist poetry, exemplified by two poems entitled ‘Vilna’, by the Hebrew poet Zalman Shneour and the Yiddish poet Moyshe Kulbak, as well as the Yiddish city guide by Zalmen Szyk, sought to restore the imaginary unity of time and space, celebrating the complexity and diversity of the city.
Keywords: Empire; First World War; nostalgia; multiculturalism; Modernism; city guides